Extension of the Alternative Intravenous Dosing Regimens of Atezolizumab into Combination Settings through Modeling and Simulation. (11th June 2022) - Liu, Stephanie N.; Marchand, Mathilde; Liu, Xiaoyan; Ingle, Gladys; Maiya, Vidya; Graupner, Vilma; Elze, Markus C.; Chan, Phyllis; Hsu, Joy C.; Lin, Alyse; Vadhavkar, Shweta; Wu, Benjamin; et al.
Abstract: Atezolizumab is approved as an intravenous (IV) infusion for use as a single agent and in combination with other therapies in a number of indications. The objectives of this publication are to characterize atezolizumab pharmacokinetics (PK) across indications with the available clinical data from one phase I and eight phase III studies, to determine the exposure–response (ER) relationships in combination settings across a variety of tumor types, and to provide the clinical safety to support the extension of the 840 mg q2w, 1200 mg q3w, and 1680 mg q4w IV dosing regimens across various indications in combination settings. Across all clinical studies, atezolizumab PK remained in the dose‐linear range and were similar across tumor types when used in combination therapy or as a monotherapy. In the combination studies, efficacy was independent of the exposures tested and there was no significant increase in adverse events with increasing atezolizumab exposure (flat ER). The safety profile of atezolizumab in the individual combination studies was generally consistent with the established safety profile of atezolizumab, the combination partners, and the disease under study. The similar atezolizumab PK across monotherapy and combination therapy settings as well as the flat ER in new tumor types and combination therapies support the use of the 3 interchangeable atezolizumab dosing regimens in the combination setting. Atezolizumab is now approved with 3 interchangeable IV dosing regimens of 840 mg q2w, 1200 mg q3w, and 1680 mg q4w for single‐agent and combination therapy use in the USA and EU.